2016
DOI: 10.1186/s12951-016-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient biodegradation of chlorophenols in aqueous phase by magnetically immobilized aniline-degrading Rhodococcus rhodochrous strain

Abstract: BackgroundChlorophenols are environmental contaminants, which are highly toxic to living beings due to their carcinogenic, mutagenic and cytotoxic properties. Bacterial degradation has been considered a cost-effective and eco-friendly method of removing chlorophenols, compared to the traditional physical–chemical processes.ResultsIn this study, we first developed an efficient process for the biodegradation of chlorophenols by magnetically immobilized Rhodococcus rhodochrous cells. R. rhodochrous DSM6263 degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…As shown by many authors, increased catalytic activities of IC could be a result of their enhanced tolerance to toxic substrates or extended cell loads achieved by immobilization [84,87]. For immobilized rhodococci, enhanced catalytic activities and increased tolerance were reported [13,40,68,[88][89][90][91], as well as the lack of significant differences with SC [70,83,85,[92][93][94][95][96]. In reference [70], the authors clearly demonstrated that, although immobilized Rhodococcus cells were similar to suspended ones and even underperformed them in catalytic activities, immobilization allowed a convenient (+4 • C, no humidity control) and long-term (12 months) storage of biocatalysts without losses in cell viability and functional activity.…”
Section: Advantages Of Immobilized Cellsmentioning
confidence: 93%
See 4 more Smart Citations
“…As shown by many authors, increased catalytic activities of IC could be a result of their enhanced tolerance to toxic substrates or extended cell loads achieved by immobilization [84,87]. For immobilized rhodococci, enhanced catalytic activities and increased tolerance were reported [13,40,68,[88][89][90][91], as well as the lack of significant differences with SC [70,83,85,[92][93][94][95][96]. In reference [70], the authors clearly demonstrated that, although immobilized Rhodococcus cells were similar to suspended ones and even underperformed them in catalytic activities, immobilization allowed a convenient (+4 • C, no humidity control) and long-term (12 months) storage of biocatalysts without losses in cell viability and functional activity.…”
Section: Advantages Of Immobilized Cellsmentioning
confidence: 93%
“…Magnetically immobilized rhodococci oxidized a target compound (2-chlorophenol) four times faster than SC or cells immobilized without magnetic nanoparticles. While particular mechanisms of these effects remain unclear, they are related perhaps to the increased contact area between cells and 2-chlorophenol, thus facilitating the substrate transfer into the cells [96]. In another work [70], rhodococcal cells were entrapped into porous ceramic-like materials.…”
Section: Choice Of the Immobilization Methodsmentioning
confidence: 99%
See 3 more Smart Citations